AKUMULASI PLAK DAN JUMLAH KOLONI BAKTERI PADA PLAK SETELAH BERKUMUR DENGAN REBUSAN DAUN SIRIH HIJAU (Piper betle Linn.) KONSENTRASI 10% - , RISTINI ASIH, drg. Tetiana Haniastuti, M.Kes., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The prevalence of periodontal disease and caries in Indonesia are very high. Both diseases are caused by bacteria that accumulated in the dental plaque i.e Streptococcus sp, Actinomyces sp, Veillonella sp, and Porphyromonas sp. Betel green (Piper betle Linn.) is a herbal plant that is commonly found in Indonesia. Betle green leaves contain alkaloid, catechin, hidroxicavicol and tannin that have antibacterial potency towards plaque bacteria. The aim of this study was to examine plaque accumulation and the number of bacterial colonies in the dental plaque after gargling using betle green leaf decoction 10%. Twenty subjects were enrolled in this study. Ten subjects gargled betel green decoction and the other gargled distilled water. Each subjects gargled twice a day, in the morning and at night for 5 days consecutively. On the first day before and the day after the treatment, sample of plaque was taken and plaque accumulation was scored with OâLeary method. The sample of plaque was cultivated on blood agar plate and incubated for 48 hours at 37Â°C. The number of bacteria colonies was then counted. Plaque accumulation was analyzed using Mann-Whitney test and the number of bacteria colonies were analyzed using independent t test (p<0.05). Mann-Whitney and independent t test showed significant different between the groups. In conclusion, plaque accumulation and the number of bacteria colonies in dental plaque were declined after gargled using Piper betle Linn. leaf decoction 10%.